If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 = 3 + -1(4 + -2) Combine like terms: 4 + -2 = 2 5 = 3 + -1(2) Multiply -1 * 2 5 = 3 + -2 Combine like terms: 3 + -2 = 1 5 = 1 Solving 5 = 1 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| -4j-3j-j+j=20 | | 23=w+6 | | 1-2tan^2x=-tan^2x | | 0.25(y-4)+.03y=0.18y-0.05(40) | | j+j-j=11 | | -16t^2+84t+112=0 | | 6.3/0.9-(-4.1)x(-0.4) | | 8y-2(5+2y)=7y-16 | | 2 = 12(9x+8) | | -3(3x-3)-9=-2(7x+3)-3 | | 16t^2+84t+112=0 | | 3x+6=27+y | | 7y+-42x+7=0 | | -8-6=7x-2-6x | | 6x-(8X+9)=2x-17 | | 9x+16y=-2 | | Sqrtx^2+7=x+1 | | 5*(x+8)=110 | | 26-u=234 | | 41.73/4.00x | | -4(3y+2x)= | | 70=164-v | | 6.78=2X/0.4-X | | 11x-67=77+2x | | x+x+1+x+2+x+3=-74 | | 3=23-5m | | -3(9+-2y+2.5z)+5y+2z=-27 | | 6(ax+3b)= | | 3+3x-1=9x+4-7x | | 14=4g-2 | | -4+(-24)=12 | | x-(3+x)+6=x-2[x-(3x+4)] |